The Effect of Digital Communication, Employee Engagement, and Trust in Management on Employee Advocacy in Gen Z Employees (Study at Coffee Shop in Blitar) - Novilia, Evita; Harwida, Gleydis; Izzah, Samlatul (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyse the influence of Digital Communication, Employee Engagement, and Trust in Management on Employee Advocacy among Generation Z employees at coffee shops in Blitar. The phenomenon of the increasing role of employees as brand advocates, especially among Gen Z, who are active on social media, encourages the need for internal organisational strategies that are able to facilitate employee engagement and loyalty. This research uses a quantitative approach with a survey method, where data is collected through questionnaires from 120 respondents. The analysis technique used was multiple linear regression. The results showed that partially and simultaneously, the three independent variables had a positive and significant effect on employee advocacy. Effective digital communication, high employee engagement, and a strong level of trust in management proved to be determining factors in shaping employee advocacy attitudes and behaviours. The findings provide practical implications for coffee shop managers in designing internal and managerial communication strategies to build sustainable employee engagement and loyalty.